2014
DOI: 10.1111/scs.12161
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of assessments and relationships of stress of conscience, perceptions of conscience, burnout and social support between healthcare personnel working at two different organizations for care of older people

Abstract: This study shows that associations between perceptions of conscience, stress of conscience and burnout are common experiences that are similar among HCP despite great differences in the characteristics of organisations. It can be burdensome for HCP to be unable to realise their ambitions to provide good care, and sex/gender can be an important factor to consider in the development of measures against the negative effects of stress of conscience. More studies are needed about how HCP's ambition to provide good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 42 publications
1
61
0
5
Order By: Relevance
“…Similarly, Choobineh et al demonstrated high levels of psychological stress among nurses because of their working conditions (39). Several studies have also indicated that factors, including job security, long-term work, shift work, lack of organizational support, and poor environmental conditions, are effective in nurses' stress (14,17); therefore, improving each of these factors can help reduce pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Choobineh et al demonstrated high levels of psychological stress among nurses because of their working conditions (39). Several studies have also indicated that factors, including job security, long-term work, shift work, lack of organizational support, and poor environmental conditions, are effective in nurses' stress (14,17); therefore, improving each of these factors can help reduce pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other occupations, healthcare personnel (especially physicians, nurses, and healthcare assistants) are more prone to burnout due to their exposure to stressors including: thanatophobia (12); interpersonal problems (13); low social support (14); verbal and physical aggression and violence (15,16); poor hospital work environments (17); high workload (18); high number of patients per day (19); decision-making in emergency situations (based on insufficient information) and accepting responsibility for the consequences (20); exertion along with mental pressure to avoid any mistakes (21); and rotating shift work, particularly night work (22). Farsi et al (2014) conducted a study at Army University of Medical Sciences (AJA) hospitals of Tehran, Iran and showed that quality of nurses' working life was reversely related to EE and DPA (23).…”
Section: Introductionmentioning
confidence: 99%
“…Employees suffer stress when demands exceed the possibilities to cope with them . Prolonged occupational stress caused by interpersonal demands may result in symptoms of burnout such as emotional exhaustion, depersonalisation and reduced personal accomplishment .…”
Section: Introductionmentioning
confidence: 99%
“…Only about 3% of the Swedish firefighters in this study scored high, which is in contrast to the general population in Sweden where nearly 20% have been reported to belong to the high-scoring group (Lindblom et al, 2006). In a recent study among Swedish healthcare personnel, about 30% scored high in EE, and about 14% scored high in DP (Åhlin, Ericson-Lidman, Norberg, & Strandberg, 2015). Among ambulance service personnel in Scotland, 25% scored high in EE (Alexander & Klein, 2001).…”
Section: Discussionmentioning
confidence: 45%